Tolerance and efficacy of palliative radiotherapy for advanced pancreatic cancer: A retrospective analysis of single-institutional experiences - WOLNY-ROKICKA, EDYTA (Mol Clin Oncol, 2016)
This study was conducted to investigate hypofractionated radiotherapy (RT) in patients with locally advanced or metastatic adenocarcinoma of the pancreas. A total of 31 patients were enrolled in this study, 26 of whom had locally advanced (M0) pancreatic cancer and 5 had metastatic (M1) disease. The patients were treated with palliative RT (6–30 Gy in 1–10 fractions over a period of 1 day-2 weeks). Treatment-related toxicity was classified according to the Common Terminology Criteria for Adverse Events, version 3.0. Early mild toxicity was observed. A total of 17 patients (55%) achieved good pain control without pharmacological therapy, and 12 patients (39%) reduced their use of analgesics; in the remaining 2 patients (6%), there was no change in analgesic use. Late high-grade (>3) toxicity was not observed. The average survival time for the 31 patients was 9 months. The 1-year overall survival rate was 16%. Palliative RT was well-tolerated and was able to prolong the survival time. The majority of the patients achieved better pain control with palliative RT.